Spacer Casting Method for Synthesis of Magnesium Alloy Foam - (:unkn) unknown (My University, 2017)
In this work, a new spacer material is developed for casting of magnesium foam. An ideal spacer material should meet the following requirements, would not react with magnesium, would withstand the melting temperature of magnesium, be easy to remove, be abundantly available and cost effective, hold its shape during infiltration, and be extrudable. The material that was found to meet these requirements was a mixture of calcium carbonate and flour that went through a heat treatment to yield a porous calcium oxide structure for infiltration. The new spacer material was extrudable and easily removed without harming the magnesium foam. Magnesium foams were produced with relative densities of 0.62-0.72. The magnesium foam showed deformation behavior typical of metal foams. The magnesium foams yield stress, 19.95-57.7 MPa, exhibited an increase to a decrease in pore size. The magnesium foams showed a linear relationship between the yield stress and the calculated relative stress, indicating valid correlation of data. Microstructures of the foams showed little evidence of grain refinement in the region of the cell walls. Some dissolution of calcium from calcium oxide was observed in the case of the smallest pore size, potentially due to the high surface area of the spacer material in that specimen.
Keywords: Magnesium Casting; Magnesium Foam; Metal Foam; Open Cell Foam; Spacer Material; Vacuum Infiltration